Relations between Loss of Services and Psychiatric Symptoms in Urban and Non-Urban Settings following a Natural Disaster - Gros, Daniel F. (2012)
Disasters have been associated with both acute and prolonged distress and significant post-disaster psychiatric symptoms. These outcomes may be further complicated by extended periods without vital services and supplies, such as electricity and drinking water. The present study investigated the relations between post-disaster loss of services and psychiatric symptoms in urban/non-urban disaster victims. Random-digit–dial methodology was used to interview 1,249 victims of Hurricane Ike, a strong storm that hit Galveston, TX in 2008. Findings demonstrated significant relations between loss of services and post-disaster symptoms of posttraumatic stress disorder (PTSD), depression, and worry. These relations varied by urban/non-urban settings; there were significant positive relations between loss of services and symptoms of depression in non-urban settings, but not in urban settings. Similarly, a stronger relation between loss of services and symptoms of PTSD also was demonstrated in non-urban compared to urban settings. Findings highlight the potential importance of pre-disaster preparation, post-disaster restoration of services, and post-disaster community support in post-disaster psychiatric outcomes, with a particular emphasis in non-urban settings.